2018
DOI: 10.11591/ijpeds.v9.i4.pp1814-1822
|View full text |Cite
|
Sign up to set email alerts
|

Wind Turbine Mounted on A Motorcycle for Portable Charger

Abstract: <span lang="EN-US">This paper aims to develop a wind energy harvesting system to charger an electronic device of 5V during traveling period from a place to another. Upon the situation faced by the two wheeler depending on the conventional power socket, this system was constructed to overcome the dependencies of power since the natural energy can be harvested to produce an electrical energy. The power storage unit system was done by integrating supercapacitor to storage the electrical energy hence an ardu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…3. Block diagram of wind energy generation system [20] One of the key benefits of wind energy is its ability to produce large amounts of electricity while releasing no greenhouse gases or other pollutants. Because of its low environmental impact, wind energy is an important role in mitigating climate change and reducing dependency on finite fossil fuels.…”
Section: B Wind Energymentioning
confidence: 99%
“…3. Block diagram of wind energy generation system [20] One of the key benefits of wind energy is its ability to produce large amounts of electricity while releasing no greenhouse gases or other pollutants. Because of its low environmental impact, wind energy is an important role in mitigating climate change and reducing dependency on finite fossil fuels.…”
Section: B Wind Energymentioning
confidence: 99%
“…The shape like an airplane propeller generally [6]. Theoretically, in the previous chapter it has been calculated that the more number of blades will allow lower drag force on the turbine surface which has the potential to rotate faster [7].The greater the wind speed then the smaller the value of efficiency obtained [8] Wind Power Plant is a system that requires wind as a source to be converted into electrical energy. The simple concept is that the wind as a source is used to rotate the pinwheel which is connected to a generator where the generator has a copper coil so that it occurs (electromotive force) [9].Of the three differences in the number of propellers, the maximum turbine generator output power value at a wind speed of 5 m/s is produced by 5 propellers with a turbine shaft output power value of 23,755 watts [10].…”
Section: Preliminarymentioning
confidence: 99%
“…C which is used to block the dc signal and then passed to transistor 1 Q which is used to amplify the voltage. The control unit is anchored by the Arduino UNO ATmega328 microcontroller which many authors including Suresh & Ahmad [23] and others [24,25,26] have employed; and reported its versatility and suitability for a wide range of applications. The program for accepting the filtered analog input signal from the EMF sensor circuit, counting the number of pulses, computing the radiation concentration, display the computed value on the display and log the data to Secure Digital (SD) card is written, compiled, tested and then uploaded to the microcontroller using the Arduino Integrated Development Environment (IDE) software.…”
Section: The Output Is Coupled To Capacitormentioning
confidence: 99%